Flipped Classroom to Improve University Student Centered Learning and Academic Performance - Ángel Custodio Mingorance Estrada; Juan Granda Vera; Gloria Rojas Ruiz; Inmaculada Alemany Arrebola (Social Sciences, 2019)
In recent years, educational research has focused on analyzing significant differences in the academic performance of university students according to the intervention model of the traditional methodology vs. the flipped classroom. This empirical-analytical research is based on a quasi-experimental design with non-equivalent groups. The results reveal significant differences on the average grades of university students; those participating in the flipped classroom obtained higher scores than students following a traditional methodology, regardless of the specialization. Moreover, this research concludes that the flipped classroom approach offers an opportunity to transform the traditional system by improving the classroom environment, the teaching-learning process and the student’s assessment.